Software defined networks : a comprehensive approach - Goransson, Paul; Black, Chuck; Culver, Timothy (Amsterdam, 2020)
This book provides in-depth coverage of the technologies collectively known as Software Defined Networking (SDN). The book shows how to explain to business decision-makers the benefits and risks in shifting parts of a network to the SDN model, when to integrate SDN technologies in a network, and how to develop or acquire SDN applications. It also emphasizes the parts of the technology that encourage opening up the network, providing treatment for alternative approaches to SDN that expand the definition of SDN as networking vendors adopt traits of SDN to their existing solutions.
Keywords: Software-defined networking (Computer network technology); Business enterprises -- Computer networks; Business -- Computer networks; Software-defined networking (Computer network technology); Rechnernetz; Verteiltes System